2020
DOI: 10.1001/jamanetworkopen.2019.20500
|View full text |Cite
|
Sign up to set email alerts
|

Association of High-Cost Health Care Utilization With Longitudinal Changes in Patient-Centered Medical Home Implementation

Abstract: IMPORTANCE In 2010, the US Veterans Health Administration (VHA) implemented one of the largest patient-centered medical home (PCMH) models in the United States, the Patient Aligned Care Team initiative. Early evaluations demonstrated promising associations with improved patient outcomes, but limited evidence exists on the longitudinal association of PCMH implementation with changes in health care utilization. OBJECTIVE To determine whether a change in PCMH implementation is associated with changes in emergency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Systematic reviews of the effectiveness of the PCMH [ 31 36 ] and individual studies [ 37 42 ] show mixed results. Sinaiko and Landrum [ 36 ] comment as follows: … Recent work identifies five domains to consider when interpreting findings of practice transformation: the practice setting, the organizational setting, the external environment, the implementation pathway, and the motivation for transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews of the effectiveness of the PCMH [ 31 36 ] and individual studies [ 37 42 ] show mixed results. Sinaiko and Landrum [ 36 ] comment as follows: … Recent work identifies five domains to consider when interpreting findings of practice transformation: the practice setting, the organizational setting, the external environment, the implementation pathway, and the motivation for transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the non-HC group, the HC population had a lower percentage of preventable ED visits and hospitalization costs, and regions with a greater density of primary care physicians reported greater levels of preventable spending for the HC population [ 12 ]. Another study also suggested that the non-HC population had over three times the rate of preventable utilization than HC patients [ 24 ]. No consistent association was found between changes in the capacity of patient-centred medical homes and the utilization of health care services among HC patients [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study also suggested that the non-HC population had over three times the rate of preventable utilization than HC patients [ 24 ]. No consistent association was found between changes in the capacity of patient-centred medical homes and the utilization of health care services among HC patients [ 24 ]. Additionally, clinics that provide complex care management did not reduce overall expenditures after discounting upfront costs [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Pi 2 score consists of 53 different elements, covering 8 domains, which are drawn from patient surveys, staff surveys, and measures of clinic operations. 1 This score has been used to assess many outcomes, covering all the dimensions of health care quality as well as staff satisfaction and burnout.…”
mentioning
confidence: 99%